Local and territorial determinants in the realization of public–private–partnerships: an empirical analysis for Italian provinces. Issue 11 (2nd November 2019) - Mazzola, Fabio; Cusimano, Alessandro; Di Giacomo, Giuseppe; Epifanio, Rosalia
ABSTRACT: Relational networks and intangible factors are crucial elements for the competitiveness of a territory. Public–Private–Partnerships (PPPs), in particular, allow for the provision of goods and services that favour the exploitation of complementarities between public and private resources. They aim at promoting an increase in the overall efficiency of investment projects through a complex mechanism that distributes risk and revenues among stakeholders. This paper examines the local and territorial determinants of PPPs through an econometric analysis based upon Italian municipal data, grouped at the provincial level. Using a tobit model, we analyse the relationship between the realization of successful PPP initiatives and different sets of factors, including less analysed local and territorial determinants. We stress the role of the local management of infrastructure assets, the administrative efficiency of local authorities and the diffusion of previous local development initiatives. Local management and territorial context factors explain most of the occurrence of successful PPP initiatives in the pre-crisis period while usual determinants (infrastructure endowment and financial distress) display a weaker effect.